Discrimination Skills Predict Effective Preference Assessment Methods for Adults with Developmental Disabilities - Lee, May S. H. (2008)
We examined the relationship between three discrimination skills (visual, visual matching-to-sample, and auditory-visual) and four stimulus modalities (object, picture, spoken, and video) in assessing preferences of leisure activities for 7 adults with developmental disabilities. Three discrimination skills were measured using the Assessment of Basic Learning Abilities Test. Three participants mastered a visual discrimination task, but not visual matching-to-sample and auditory-visual discriminations; two participants mastered visual and visual matching-to-sample discriminations, but not auditory-visual discrimination, and two participants showed all three discriminations. The most and least preferred activities, identified through paired-stimulus preference assessment using objects, were presented to each participant in each of the four modalities using a reversal design. The results showed that (1) participants with visual discrimination alone showed a preference for their preferred activities in the object modality only; (2) those with visual and visual matching-to-sample discriminations, but not auditory-visual discrimination, showed a preference for their preferred activities in the object but not in the spoken modality, and mixed results in the pictorial and video modalities; and (3) those with all three discriminations showed a preference for their preferred activities in all four modalities. These results provide partial replications of previous findings on the relationship between discriminations and object, pictorial, and spoken modalities, and extend previous research to include video stimuli.